China-India Engagement : Towards A New-Normal? - Suryanarayana, P. S. (2018)
Sino-Russian bonhomie enables India to become a member of Shanghai Cooperation Organisation at Moscow’s initiative and China’s welcoming manner. India’s entry may catalyse a new strategic variable in today’s polarising geopolitics.